RETRACTED ARTICLE: Study on Esterification Reaction of Starch Isolated from Cassava (Manihot Esculenta) with Acetic Acid and Isopropyl Myristate Using Ultrasonicator - Amini, Helda Wika; Masruri, Masruri; Ulfa, Siti Mariyah (The Journal of Pure and Applied Chemistry Research, 2017)
This article has been retracted at the request of managing editor.REASON: One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not prepared and/or appeared in any other publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.Similar article has appeared inÂ http://iopscience.iop.org/article/10.1088/1757-899X/299/1/012079/pdfÂ